Media Studies and Politics in Indonesia: a Systematic Literature Review - Saputra, Gemilang Bayu Ragil; Nurliana; Sari, Dyah Fitria Kartika; Kudratullah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to systematically map the themes, trends, and gaps in media and political studies in Indonesia between 2020 and 2025. The method used was a systematic literature review (SLR) guided by the PRISMA framework. The dataset was collected through the Scopus/ScienceDirect database using specific keywords. The initial data collection yielded 98 entries. After screening and eligibility assessment, the clean data yielded 32 entries. The dataset was analysed using the bibliometrix tool in RStudio. The analysis showed that the phrase "palm oil" was the most dominant keyword, followed by "public health" and "social media." This finding indicates a cross-sectoral dimension in media-political studies. The trend analysis revealed three thematic phases: the dominance of the pandemic and news media issues (2020), a shift to public health, the environment, and religion (2021-2023), and the strengthening of social media, child marriage, and sentiment analysis (2025). The co-occurrence network revealed three main clusters: media and digital studies, empirical research and public data, and global policy and trade. We also found that there is a significant gap between the academic agenda and actual political dynamics.